Paul Ricouer: entre hermenêutica e crítica das ideologias - Almeida, Ana Kelly de (2007)
This work exposes the Paul Ric ur s thought in relation to the contemporary complaint between the hermeneutics and the ideologies criticism. It shows, in this direction, the unity between text and action according to Ric ur s perspective. The philosophical view of Ric ur, It affirms, is far from any eclecticism, but if it characterizes for a dynamic style, explained here from the analogies with the movement of the particles, of the quantum physics, which help to excuse to the make a mistake idea of compilation and eclecticism, resultant of superficial readings of its texts. In deep, this work nothing more it is that a contribution to the construction of a theory of the reading of the text of this notable philosopher